Progressive Muscle Relaxation (PMR) Training For Family With Pregnant Mothers As An Effort To Increase Attendance To The Impact Of Pandemic In Tasikmalaya - Sofia Februanti; Tetet Kartilah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Community health center (puskesmas) is the front line in providing health services to the community, including pregnant women. However, during the Covid-19 outbreak, forcing people to keep their distance from other people, wear masks, and prevent crowds, Puskesmas has been unable to optimally provide health services to pregnant women who will check their pregnancies. In addition, the long and uncertain pandemic situation, and the high potential for transmission are stressors that can have an impact on discomfort in the form of anxiety and fatigue for pregnant women which will encourage various problems during pregnancy until delivery. Therefore, the purpose of this community service is to increase the knowledge, attitudes, and skills of pregnant women and their families and the cadres in reducing the level of fatigue due to pregnancy, through planned training activities, increasing public awareness, and participation in maintaining the health and welfare of pregnant women as an effort to reduce morbidity. pregnant mother. The action was carried out in Setiawargi village, Tamansari Tasikmalaya. The method used is training in small groups directly using demonstration techniques by devotees and red demonstrations by pregnant women and the cadres. The media used for the training were audio-visual presentations about the concept of changes in pregnancy, videos on how to do PMR, and reading materials in the form of leaflets and pocketbooks. The activity results showed an increase in the knowledge and skills of pregnant women and their families, and the cadres after the training activities were carried out.